Child welfare social work : an introduction - Popple, Philip R. 4 0 16; Vecchiolla, Francine J.; 5 (Boston : Pearson/Allyn and Bacon, 2007)
Child Welfare Social Work is a brief, introductory text for child welfare courses covering the most important policy and practice issues.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Child welfare.;Social work with children.;Social case work with children. -- 20; 20; 2